Determining the association between different living arrangements and depressive symptoms among over-65-year-old people: The moderating role of outdoor activities - Xu, Rixiang; Liu, Yulian; Mu, Tingyu; Ye, Yaping; Xu, Caiming (Frontiers in Public Health, 2022)
Background China is presently facing the challenge of meeting enormous health demands because of its rapidly aging society. Enrolling older persons in eldercare institutions is a helpful alternative for relieving family caregivers and promoting healthy aging. However, changes in the living environment may negatively affect the mental health of the elderly. Objective To explore the association between different living arrangements and depressive symptoms among over-65-year-old people in China and the moderating role of outdoor activities. Method The 2018 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) used a mixed sampling method to collect the health and demographic information of 15,874 older adults over 65 years from 23 provinces in China. After considering this study's inclusion and exclusion criteria, the final sample comprised 12,200 participants. The participants' risk of depressive symptoms was assessed using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10). The potential association between the two elements was tested using a regression model. Result This study's findings suggested a significant relationship between depressive symptoms and living arrangements (P < 0.001). Participants living alone and those living in eldercare institutions had 1.26-times (95%CI: 1.10–1.44) and 1.39-times (95%CI: 1.09–1.77) higher risks of depressive symptoms, respectively, than those living with household members. Outdoor activities play a moderating role between different living arrangements and depressive symptoms. Among participants who engaged in outdoor activities, no significant difference was observed in the risk of depressive symptoms between those living in eldercare institutions and those living with household members (adjusted odds ratio = 1.15, 95%CI = 0.81–1.64, P = 0.426). Conclusion The high risk of depressive symptoms among older Chinese people living alone or in eldercare institutions requires considerable attention. The evidence from this study suggests that older people living alone and those living in eldercare institutions should regularly engage in appropriate outdoor activities.